Small area estimates of the low work intensity indicator at voivodeship level in Poland - Łukasz Wawrowski; Maciej Beręsewicz (Statistics in Transition New Series, 2021)
The EU Statistics on Income and Living Conditions (EU-SILC) has provided annual estimates of the number of labour market indicators for EU countries since 2003, with an almost exclusive focus on national rates. However, it is impossible to obtain reliable direct estimates of labour market statistics at low levels based on the EU-SILC survey. In such cases, modelbased small area estimation can be used. In this paper, the low work intensity indicator for the spatial domains in Poland between 2005-2012 was estimated. The Rao and You (1994), Fay and Diallo (2012), and Marhuenda, Molina and Morales (2013) models were applied. The bootstrap MSE for the discussed methods was proposed. The results indicate that these models provide more reliable estimates than direct estimation.
Keywords: 519; EU-SILC; low work intensity; labour market; small area estimation; temporal models; spatio-temporal models